1989
DOI: 10.1007/bf01648551
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and functional outcome after restorative proctocolectomy

Abstract: One hundred consecutive patients treated by restorative proctocolectomy with construction of an ileo-anal anastomosis and a J-shaped (n = 90) or an S-shaped ileal reservoir were studied prospectively to evaluate postoperative complications and functional outcome and to search for factors that might influence results. There were no deaths. Postoperative complications requiring surgery were pelvic sepsis (3 patients), pouch-related fistula (2), peritonitis following ileostomy closure (3) and small bowel obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
2
10

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(113 citation statements)
references
References 28 publications
4
97
2
10
Order By: Relevance
“…There is much confusion surrounding pouchitis because the syndrome has not been tightly defined. The reported incidence of pouchitis varies widely between 7% and 42% (3,4,10,11,(41)(42)(43)(44)(45)(46)(47)(48)(49). This variation can partly be explained by whether or not endoscopic and histologic confirmation was required to establish a diagnosis of pouchitis (Table III).…”
Section: Pouchitismentioning
confidence: 99%
“…There is much confusion surrounding pouchitis because the syndrome has not been tightly defined. The reported incidence of pouchitis varies widely between 7% and 42% (3,4,10,11,(41)(42)(43)(44)(45)(46)(47)(48)(49). This variation can partly be explained by whether or not endoscopic and histologic confirmation was required to establish a diagnosis of pouchitis (Table III).…”
Section: Pouchitismentioning
confidence: 99%
“…Shoetz et al [4] reported that 3 of 142 J pouch patients developed the APB syndrome before ileostomy closure. However, Oresland et al [5] reported that 6 of 100 J pouch patients had this syndrome as a late compli cation after stomal closure. All our cases of APB syn drome also occurred as a late complication of IAA.…”
Section: Discussionmentioning
confidence: 99%
“…Schoetz et al [4] and Oresland et al [5] have also reported that an apical pouch bridge can cause outlet obstruction of the J pouch. This bridge is a residual septum which remains at the apex of the J pouch.…”
Section: Introductionmentioning
confidence: 99%
“…Se defi ne como falla del reservorio la necesidad de una ileostomía permanente con o sin extirpación del reservorio debido a síntomas intratables o complicaciones. Los resultados funcionales de la intervención fueron evaluados mediante el score de Öresland 7 , que va de 0 a 15 puntos (0 es perfecto, 15 malo) mediante entrevista. Un puntaje de 0 a 3 se considera como función satisfactoria, de 4 a 6 aceptable y de 7 o más como defi ciente.…”
Section: Pacientes Y Métodounclassified